Which algebraic rule describes the transformation?

A) (x, y) → (x + 1, y − 3)

B) (x, y) → (x + 3, y − 1)

C) (x, y) → (x − 1, y + 3)

D) (x, y) → (x − 3, y + 1)

Which algebraic rule describes the transformation A x y x 1 y 3 B x y x 3 y 1 C x y x 1 y 3 D x y x 3 y 1 class=

Respuesta :

I think its C im not sure tho

Answer:

It's B.

Step-by-step explanation:

(x, y) ---> (x + 3, y - 1)

Using point X as an example:

(x, y) ---> (x + 3, y - 1)

(0, 0) ---> (0 + 3, 0 -1)

(0, 0) ---> (3, -1)

ACCESS MORE